Anthropometric measurements and agility performance in amateur roller skaters: a correlational study - Salekar, Bhagyashree C.; Palekar, Pramod; Bhawsar, Pooja; Palekar, Tushar J. (International Journal of Research in Medical Sciences, 2024)
Background: Research on the body structure of roller skaters has identified that anthropometric attributes are desirable in this sport for a better performance. Leg length has a definite decisive advantage in sport. Explosive leg power is very essential for roller skating as it requires speed, agility and quickness which can be associated with lower limb muscle girth. Hence, it is important to examine the contribution of limb length, calf and thigh muscle circumference, to agility performance. Methods: 30 healthy amateur roller skaters within age group of 6 to 14 years were assessed for anthropometric measurements – lower limb length, thigh circumference, calf circumference measurement. Participants performed a standardized warm-up of moderate-intensity jogging (5-10 min), static and dynamic stretching (5 min) and brief bouts of high-intensity running, including changes in direction on the ground. They performed agility tests in order of Edgren side step test, t-test and Illinois agility test based on test direction, progressing from uniplanar movements to biplanar and concluding with multidirectional movements. Each test was performed twice with 1-minute rest period between each trial, and a 2 min rest period between each test. Results: Pearson’s correlation showed that lower limb length have a moderately positive correlation with agility (r=0.5-0.7) whereas calf and thigh muscle circumference have a strong positive correlation with agility (r=0.7-0.8) stating that anthropometric measurements have a statistically significant correlation with agility performance with p<0.05. Conclusions: Anthropometric measurements such as lower limb length, thigh and calf circumferences have a moderate to strong positive correlation with agility performances of healthy amateur roller skaters within the age group of 6-14 years..